Coriander leaf essential oil as an immunomodulator: Enhancing NF-κB-driven RAW246.7 murine macrophages response to Candida albicans - Pratsanee Hiengrach; Pasinee Sangsiwarit; Waewta Kuwatjanakul; Kittipan Samerpitak; Pitchaya Luksanawilas (PLoS ONE, 2026)
Coriander is a cultivated aromatic herb used as a culinary ingredient and in traditional medicinal treatments worldwide. Coriander essential oil contains various bioactive constituents with antibacterial, antioxidant, and anti-inflammatory effects. The oil also has antifungal activity against Candida albicans, the most common opportunistic fungal pathogen causing infections at various body sites. Furthermore, the oil can increase macrophage phagocytic activity. However, its effect on other macrophage functions during C. albicans infection is still unclear. This study aims to investigate the effect of coriander leaf essential oil on macrophage activity via the NF-κB gene expression during C. albicans infection. RAW264.7, a murine macrophage cell line, was cultured with viable C. albicans , either in the absence or presence of the oil (0 − 50 μg/mL). The fungal killing activity, pro- and anti-inflammatory cytokine production, and NF-κB gene expression were assessed. Our results revealed the potential of coriander leaf essential oil as an immunomodulator that enhances macrophage responses to C. albicans via the activation of the NF-κB gene. These findings may help to further the development of coriander leaf essential oil as an adjuvant antifungal and immunomodulatory medication.